2003
DOI: 10.2320/jinstmet1952.67.9_452
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Aluminium Alloy Casting Melted using a Cold-Crucible Furnace

Abstract: Although many investigations on the mechanical properties of aluminum alloy castings have been performed, there have been few investigations that make positively good use of the effect of impurities reduction. In this study, the influence of impurities on the tensile properties of aluminum alloy casting has been investigated by using aluminum alloy castings of different purity.Al Si Mg alloy castings were melted by cold crucible furnace using the commercial high purity metals. The chemical composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These findings reveal that a lot of the large-scale fracture occurred at the interface between -phase and eutectic silicon in L-Alloy, and we surmised that the binding-strength of interface betweenphase and eutectic silicon in L-Alloy might be weaker than that in H-Alloy. In a previous investigation which the present authors have carried out, 7) the improvements of elongation for -phase and binding-strength of interface betweenphase and eutectic silicon in eutectic structure were thought to be the causes of large elongation for AC4CH-T6 by purification. The both alloys of this study extensively reveal the eutectic structure and the eutectic structure exhibits an appreciable difference between them.…”
Section: Effect Of Purity On Hardness and Tensile Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings reveal that a lot of the large-scale fracture occurred at the interface between -phase and eutectic silicon in L-Alloy, and we surmised that the binding-strength of interface betweenphase and eutectic silicon in L-Alloy might be weaker than that in H-Alloy. In a previous investigation which the present authors have carried out, 7) the improvements of elongation for -phase and binding-strength of interface betweenphase and eutectic silicon in eutectic structure were thought to be the causes of large elongation for AC4CH-T6 by purification. The both alloys of this study extensively reveal the eutectic structure and the eutectic structure exhibits an appreciable difference between them.…”
Section: Effect Of Purity On Hardness and Tensile Propertymentioning
confidence: 99%
“…The present authors reported that there was a possibility of improving the elongation by purification without remarkable decreasing of the tensile strength for AC4CH. 7) However, the cause of large elongation has not been clarified yet. Also it was reported that the mechanical properties of Al-Si system alloy are affected by eutectic solidification structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation